DNA Nanostructures and DNA‐Functionalized Nanoparticles for Cancer Theranostics - Nicolson, Fay (Adv Sci (Weinh), 2020)
In the last two decades, DNA has attracted significant attention toward the development of materials at the nanoscale for emerging applications due to the unparalleled versatility and programmability of DNA building blocks. DNA‐based artificial nanomaterials can be broadly classified into two categories: DNA nanostructures (DNA‐NSs) and DNA‐functionalized nanoparticles (DNA‐NPs). More importantly, their use in nanotheranostics, a field that combines diagnostics with therapy via drug or gene delivery in an all‐in‐one platform, has been applied extensively in recent years to provide personalized cancer treatments. Conveniently, the ease of attachment of both imaging and therapeutic moieties to DNA‐NSs or DNA‐NPs enables high biostability, biocompatibility, and drug loading capabilities, and as a consequence, has markedly catalyzed the rapid growth of this field. This review aims to provide an overview of the recent progress of DNA‐NSs and DNA‐NPs as theranostic agents, the use of DNA‐NSs and DNA‐NPs as gene and drug delivery platforms, and a perspective on their clinical translation in the realm of oncology.